Creation of Entrepreneurship through Public Private Partnerships – A success story from North Eastern India - Thomas, R; H, Mohan N; Rajkhowa, S (Indian Farming, 2020)
Public-private sector partnership (PPP) is an institutional innovation to bring in synergy, mobilize resources, generate, validate and transfer technologies. In every PPP programme, skills and assets of each sector (public and private) are shared in delivering a service or a facility for the use of the general public through a mutual agreement. In addition to sharing of the resources, each party also shares risks and rewards potential in the delivery of the service and/or the facility. Across the world, lot of innovations of technologies/techniques are happening in the R&D institutions, including that of agriculture and allied sectors, but their outreach to the end user is very much limited. In order to achieve efficient transfer of technologies from research institution to the industry, partnerships at various levels with different objectives were developed amongst various stakeholders, which shall bring prosperity to the nation through the prosperity of the main stakeholder, the farmer. For the success of the partnership with Public Institutions and Private Organizations, identifying the strengths of the partner and the areas of complementarities are very important. With partnership between public and private sectors, the strengths of both the sectors are leveraged. On one hand, public sector has highly skilled and efficient manpower in agriculture and on the other hand, private sector has excellent managerial resources. Private extension would improve commercialization of technology and make it available at the global level. The decentralized decision-making in private sector helps in reducing time for commercialization.